Strażnik demokracji czy relikt przeszłości? Dyskusje nad zasadnością stosowania ciszy wyborczej - Zaborski, Marcin (Political Preferences, 2013)
The artic1e focuses on the issue of e1ection si1ence, the range of its app1i- cabi1ity and significance for the Po1ish democratic system. It describes in detai1 the 1ega1 perspective of the phenomenon at the same time i11ustrating its actua1 impact on the functioning of party competition and e1ectora1 decision-making process.The primary goa1 of this paper is to present the resu1ts of empirica1 studies on the importance of pre-e1ection po11s for the deve1opment of the actua1 support of voters. Empirica1 verification has been app1ied to a thesis which assumes that the pub1ication of opinion po11s in support of candidates or po1itica1 parties during e1ection campaigns shou1d be forbidden 1onger than just during e1ection si1ence. The resu1ts were a1so corre1ated with the dec1ared po1itica1 preferences of the respondents, which a11owed the author a more detai1ed ana1ysis of the revea1ed regu1arities.